ANALYSIS OF MAN-HOUR REQUIREMENTS AND SCHEDULING FOR FLOATING DOCK REPAIRS - Ramadhani, Salsabila; Hardiyanti, Fitri; Suhardjito, Gaguk; Soelistijono, Rachmad Tri; Wahidin, Aang (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2023)
A floating dock (FD) is a platform for ship construction and repair. Structural damages to a FD can significantly reduce ship docking productivity, leading to substantial losses for shipyard companies. In order to restore its operational capabilities, repairing the damaged FD becomes essential. This research aims to plan and analyze the schedule to ensure the efficiency and effectiveness of FD repair activities. The process begins with the establishment of a Work Breakdown Structure (WBS), followed by determining the required man hours (MH) and scheduling using the Precedence Diagram Method (PDM). Finally, the S-curve is made for monitoring the progress of the FD repairment. The findings of this study, based on a case study involving a 6700 TLC FD, reveal a WBS comprising 66 repair tasks including two tasks for FD testing and finishing in addition to four areas of hull, walls, deck and tanks, piping systems, and machinery. The MH requirement for these tasks is 4048 MH. From the scheduling results, it was found that the duration was 12 days, with a total of 53 critical activities and 25 critical paths in the floating dock repair work using the precedence diagram method.